First-principles Investigation on the Electronic Structures of Anatase TiO2 codoped with Nitrogen and 3d Transition Metals - Shukri, Ganes; Afifah, Hasna; Gandaryus Saputro, Adhitya; Kresno Dipojono, Hermawan (Journal of Research and Development on Nanotechnology, 2021)
By means of first-principles density functional theory (DFT) calculations, we study the effect of introducing Nitrogen and 3d transition metals (viz., Cr, Mn, Fe, Co, Ni) as a pair of co-dopants to the electronic structure of anatase TiO2. Herein, our attempt is to mapped the pattern of the impurity states emergence on the band structures and density of states of anatase TiO2 for spesicif application such as photocatalysis water splitting. Based on the obtained results, TiO2 codoped with (N,Co) or (N,Fe) pairs are expected to be more active and efficient photocatalyst compared to pristine anatase TiO2 due to their synergistic effect of dopant pairs in lowering the overall anatase TiO2 band gap and simultaneously hindering the possibility of early charge recombination.